WORKING WITH AUTISM CHILDREN USING ACUPUNCTURE METHOD - Remanlay, Henry (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Autism is a disorder with symptoms as a failure to develop normal social interaction with other people, impaired of communication and imaginative ability, followed by repetitive and stereotyped movements. Autism is a global issue that may a possible cause of generation lost, and economic burden to a country. Acupuncture as one of TCM (Traditional Chinese Medicine) technique is an option to improve the life quality of children with Autism. Purpose: To determine the syndrome pattern of children with autism and how acupuncture method works for children with autism, from the perspective of TCM. Method: Four examination methods are incorporated into nine ongoing-treatment subjects fit in autism classification from randomized special need cases. Subject characteristics are derived from allo-anamnesis. Needle acupuncture was the method of choice except one subject prefers laser acupuncture. The objective is to eliminate the phlegm, calm the heart fire, and tonify spleen. Result: after 3-5 sessions of treatment, parents reported speech improvement and reduction of compulsive self-stimulation behavior. Four subjects demonstrated speech improvement, 1 subject showed better focus and concentration, 1 subject indicated a reduction of compulsive self-stimulation behavior, 1 subject improved in obedience and improved comprehension was found in 2 subjects. Conclusion: Observation on nine subjects showed in general that they had phlegm harassing the heart and digestion problem due to spleen deficiency. This phlegm disturbed the heart functions, i.e. mental capacity including speech. Results from the treatments showed elimination of phlegm, cooling down the heart fire, and tonification of spleen improved speech, focus, comprehension, obedience, and reduction of compulsive self-stimulation behavior. Further research and study from the Chinese medicine perspective are needed.